A recepção de ciberpoemas: experiência de navegação no site de Sérgio Capparelli na escola - Gomes, Renata Gonçalves (2017)
The educational field, as well as several other spheres of society, go through changes influenced by digital tools of information and communication technology (ICT) available to the digital generation (TAPSCOTT, 2010). Children's and youth literature also found in digital technologies field for the literary text. Based on these statements, this paper aims to observe the navigability and analyze the appreciation of seventh-year students of elementary school in a public school by their cyberpoems in Ciberpoesia´s webpage by Sérgio Capparelli and Ana Cláudia Gruszynski. This academic work is therefore justified by the purpose of constituting analytical material regarding the navigation and reception of cyberpoems, as well as the creation of a theoretical contribution that corroborates with other researches related to the aesthetics of digital poems. To develop this investigative research, it was used the qualitative participant research in which children integrated a Reading Workshop in a computerized room of the school, where they are regularly enrolled. The analysis presented in this research are based on a theoretical contribution related to hypertext (NOJOSA, 2012), reading and the digital media (HAYLES, 2009; SANTAELLA, 2013), discussed in the first chapter. The second chapter presents Capparelli.com.br platform and deals with the issues related to cyber culture and the reader’s formation (LEMOS, 2013; LEVY, 2000). The last chapter reserves to the presentation of the methodology that follows the assumptions of the participant research (DEMO, 1982), the navigation (SANTAELLA, 2004) and subject’s appreciation by cyberpoems research (JAUSS, 2002). It comes to the final considerations with the understanding that cyberspace forms an intersemiotic digital literary gender and that, although constituting the digital technologies cultural influence, still lacks from different technical and technological supports, and pedagogical mediation to integrate school practices.